Pengaruh Ukuran Perusahaan, Debt To Equity Ratio, Dan Current Ratio Terhadap Kebijakan Dividen Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2019-2023 - Sindi Ayu Rahmayani; Desi Ika; Rizki Fillhayati Rambe (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effects of firm size, the Debt-to-Equity Ratio, and the Current Ratio on dividend policy and profitability. This study aims to partially examine the mediating effect of profitability in mediating the relationship between firm size, the Debt-to-Equity Ratio, and the Current Ratio, and its impact on dividend policy. The sample size in this study consisted of 135 observational data points from manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The analytical technique used was path analysis. The results indicate that firm size and the Debt-to-Equity Ratio have a positive and significant impact on profitability. In contrast, the Current Ratio does not have a significant effect on profitability. Firm size and the Debt-to-Equity Ratio have a positive and significant impact on dividend policy, while the Current Ratio does not affect dividend policy. Profitability does not mediate the relationship between firm size, the Debt-to-Equity Ratio, and the current ratio in determining dividend policy in manufacturing companies listed on the IDX for the period 2019-2023.